KARAKTERISTIK EKONOMI RUMAH TANGGA DAN RELEVANSINYA DENGAN KONSEP EKONOMI SYARIAH (Analisis Empiris Peran Ibu Rumah Tangga Sebagai Pekerja Sektor Informal di Provinsi Banten) - Wazin, Wazin (ALQALAM, 2018)
The purpose of this study is to determine the economic role of housewives as workers in the informal sector and to recognize the economic characteristics of households related to the role of housewives as workers in the informal sector. This study uses a qualitative descriptive research methodology approach with a case study. The results of the study prove that: 1) The economic role of housewives as workers in the informal sector is to meet family needs; flexible informal sector employment allows housewives to prioritize the work of their domestic sector; positive values that support the economic role of housewives according to the concept of Islamic economy is the level of consumption satisfaction not on desires, but on the needs and considerations of benefit. 2) Economic characteristics of family households related to the economic role of housewives as workers in the informal sector are as follows; suppressing primary needs for allocation in prioritized secondary needs, such as education and transportation, saving is saved not for investment purposes but for the reserve of extra expenses, current expenditure is not always equal to current income, but is also based on expectations of future income.Keywords: Women, Informal Sector, Household Economy, Islamic Economy, Syariah, Banten